Antitrust Law in the BRICS Countries: A Review and Critique - N. Kumar (BRICS Law Journal)
A growing trend shows that global economic power is shifting away from the United States and Europe and towards the BRICS nations. The BRICS nations are predicted to hold the dominant position in the world by 2050. The rapid development of these economies and their markets is also raising a serious concern for the national antitrust enforcement authorities of the BRICS countries in their respective jurisdictions. This study attempts to examine the effectiveness of antitrust law, with a special focus on new developing trends in each of the BRICS jurisdictions. In addition, the study examines the proposed changes and limitations of the Indian Competition (Amendment) Bill 2022. The study reveals that the national antitrust laws and their enforcement processes are not fully developed and in need of considerable changes. Furthermore, the study indicates that while the proposed Amendment Bill 2022 is a progressive step in the right direction, it fails to cover certain key areas of the digital era, requiring further modifications to anticipate future impacts of economic development. In conclusion, the author recommends some points for effective policymaking, along with their future implications.